Marketplace Platform Providers as Income Tax Collectors: Proposal For Indonesia - Rizki Desima Renova Siahaan; Yulianti Abbas (Greenation Research & Yayasan Global Resarch National, 2025)
This study proposes a policy to appoint marketplace platform providers as income tax (PPh) withholding agents. The proposed policy is designed and evaluated based on the OECD (2015) principles: Neutrality, Efficiency, Certainty & Simplicity, Effectiveness & Fairness, Flexibility, and Equity. The research uses a descriptive qualitative method with a case study approach. Data was collected through interviews and literature review. Interviewees included officials from the Directorate General of Taxes (DJP), the Fiscal Policy Agency (BKF), marketplace platform providers, and merchants.The results show that appointing marketplace platforms as income tax withholding agents reduces administrative and compliance costs for merchants, simplifies tax obligations, prevents calculation and payment errors, and increases taxpayer compliance. The policy is relevant to the current digital economy. Nevertheless, implementing the policy for transactions outside of marketplace platforms remains a challenge. Additionally, the policy needs to align with Government Regulation (PP) No. 55 of 2022 is essential to maintain fairness. Overall, the policy meets the OECD (2015) principles of Efficiency, Certainty & Simplicity, Effectiveness & Fairness, Flexibility, and Equity. It does not yet fulfill the principle of Neutrality.